IMPLEMENTING THE SOBRY LEARNING MODEL AND GAME TO IMPROVE STUDENTS’ ABILITY IN ENGLISH LANGUAGE TEACHING - Eni, Genoveva Dua; Sulaiman, Eugelin (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aimed to find out the students’ ability to learnEnglish vocabulary through the implementation of the SOBRY Learning Model and game and to find out the problemsencountered by students in learning English. This research was an action research. The research was carried out in the English LanguageEducation Study Program, Faculty of Teacher Training and Education, Nusa Nipa University. The research subjects were 23 students from first-semester students in the English Language Education Study Program. In collecting the data, the researcher used written interviews and tests. This research found that there were several problems faced by the students, namely lack of vocabulary, some of them could easily follow the writing exercises but some still confronted difficulties in doing exercises, and they did not choose the appropriate words. The researcher concluded that the implementation of the SOBRY Learning Model and a game could improve students’ ability in English language teaching as part of innovation in education.